Indonesian Creative Economy Performance In 2015-2020 - Dyastiarini, Astri; Hendrayati, Sri Lestari; Yuni, Sri; Fransiska, Christina (Perpustakaan dan Penerbitan Unismuh Makassar, 2024)
The creative economy is a sector that makes a large contribution to Indonesia's GDP. When the pandemic outbreak weakened Indonesia's economy, the creative economy sector continued to grow in several sub-sectors. The purpose of this study is to assess the performance of the creative economy in Indonesia during the 2015-2020 period and assess Indonesia's potential to develop the creative economy sector. This study uses descriptive analysis and qualitative methods with interpretation of statistical data from eight main factors of creative economy performance. The results of the study show that Indonesia has great potential to develop the creative economy sector by strengthening the factors of education, leadership, infrastructure, culture, government policies, technological innovation, creative clusters/networks, and diversity.